Introduction of the genetic counseling profession by teachers in BIPOC‐majority high schools. Issue 2 (4th November 2022) - Sveden, Abigail; Schwartz, Alison; Breen, Katelyn; Gochyyev, Perman; Channaoui, Nadine
Abstract: The field of genetic counseling is racially and ethnically (RE) homogenous, with 90% of genetic counselors identifying as white. As awareness of genetic counseling increases interest in the career, one proposed method to increase the profession's RE diversity is to introduce genetic counseling as a career option to Black, Indigenous, and people of color (BIPOC) students during high school. This study explores the knowledge, presentation, and perceptions of the genetic counseling profession by high school teachers at BIPOC‐majority high schools in the United States (US). Science teachers working at public high schools in Massachusetts and New York where greater than 75% of the student body identifies as BIPOC were invited to participate in a survey and focus groups for this study. A total of 456 teachers participated in the survey and a total of seven teachers participated in two focus groups. The survey data revealed that most (91.8%) participating teachers presented genetic counseling, though BIPOC‐identifying teachers were more likely to report never presenting genetic counseling than white‐identifying teachers. In addition, teachers' knowledge of the genetic counseling career and frequency of presenting it were strongly associated, suggesting that increasing knowledge of genetic counseling among teachers, particularly those who are BIPOC‐identifying, could lead to increased presentation to BIPOC students. Major themes that emerged through the focus groups included (1) teachers perceiving genetic counseling as novel and complex in comparison to other healthcare professions, (2) teachers sharing that multiple methods can and should be used when introducing genetic counseling to students, and (3) the notion that teachers could have an important role in introducing genetic counseling to their students. Considering findings from the survey and focus groups, recommendations from this study include increasing awareness of genetic counseling among BIPOC‐identifying science teachers at BIPOC‐majority high schools, gradually introducing genetic counseling topics to students beginning at a young age, and utilizing student‐led teaching activities.